2023
DOI: 10.2174/1389557523666230106120302
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Soluble CD163 and its Diagnostic and Prognostic Value in a Variety of Neurological Disorders

Abstract: Nowadays, many people suffer from Neurological Diseases (NDs), particularly neurodegenerative diseases. Hence, there is an urgent need to discover new and more effective diagnostic and prognostic biomarkers as well as therapeutic strategies for the treatment of NDs. In this context, detecting biomarkers can provide helpful information on various levels of NDs. Up to now, there has been a lot of progress in recognizing these diseases, but they are not completely clear yet. NDs are associated with inflammatory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 105 publications
0
5
0
Order By: Relevance
“…There are drugs for other diseases that regulate sCD163 production. 16 It would also be of interest to explore the association between sCD163 and the progression of DR in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are drugs for other diseases that regulate sCD163 production. 16 It would also be of interest to explore the association between sCD163 and the progression of DR in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“… 15 The enzymes ADAM17/TACE and ADAM10 contribute to increased shedding of sCD163 from macrophages. 16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated the association of Semaphorin-7A (Sema7A) with various diseases such as multiple sclerosis lesions [ 16 ], rheumatoid arthritis [ 17 ], acute aortic dissection [ 18 ], etc. It has been reported that CD163 may be a potential biomarker for infectious diseases [ 19 ], immune diseases [ 20 ], tumors [ 21 ] and Neurological Disorders [ 22 ]. Sema7A [ 23 ] and CD163 [ 24 ] have elevated expression in response to inflammation, and they both play a role in atherogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Also, neurological diseases are associated with inflammatory conditions and several differences in the levels of biomarkers in neurological diseases compared to normal conditions were reported [ 33 ]. Among these biomarkers, soluble CD163 (sCD163) levels increase in both CSF and plasma samples, related to the activation of macrophage/microglia and inflammation levels in neurological diseases, supporting its role also as a cognitive impairment biomarker [ 34 , 35 , 36 , 37 ]. sCD163 is a soluble form of CD163, a receptor for haptoglobin–hemoglobin complexes and a monocyte/macrophage-specific membrane protein.…”
Section: Introductionmentioning
confidence: 99%